Cognitive linguistics approach to the representation of knowledge contents in college English textbooks - Zhang, Li; Mo, Zaishu (Frontiers in Psychology, 2026)
This paper proposes a metaphor-based textbook analysis model from a macroscopic perspective and abstracts it with the “Source–Path–Goal (SPG)” image schema. Seeking new insights from cognitive linguistic theory, as well as conceptual metaphor theory (CMT), this research probes into the source, path, and goal of the metaphorical representation of knowledge contents in a series of college English textbooks in China. With the construction of a self-built textbook corpus and the aid of an online corpus annotation tool, qualitative content analysis was carried out to uncover the metaphorical representations in the textbook texts and tasks. Findings show that first, the conceptual metaphors in the texts and the metaphorical analogical reasoning in tasks are considered in the analysis model as “Source.” Second, structured design including the “hourglass” pattern in the unit design is the “Path” of knowledge representation in the textbooks. Third, the functions of these metaphorical representations are discussed as the “goal” of the knowledge representations in the textbooks, which is the realization of competence development as the textbooks’ teaching objectives. Since conceptual metaphor theory puts forward a universality of metaphors, the case study is not only typical in the Chinese context but also potentially informative beyond it.